Cefcanel Daloxate versus Penicillin in Acute Streptococcal Pharyngotonsillitis. (1994) - Grunfeld, A; Sinclair, P; Nicolle, LE; the Canadian Tonsillitis Study Group,
Abstract : Objective: To determine the efficacy, safety and tolerance of cefcanel daloxate and phenoxymethylpenicillin (PcV) in the treatment of acute pharyngotonsillitis caused by beta-hemolytic streptococci group A (bhsga ). Patients and Methods: Randomized, double-blind, multicentre study with subjects randomized 1:1:1:1 to four parallel treatment groups: cefcanel daloxate 150 mg bid, 300 mg bid, 600 mg daily and PcV 300 mg tid. Patients were treated for 10 days with clinical, bacteriological and safety evaluation at inclusion, during therapy (day 5), early after completion of therapy (day 14) and two weeks later (day 28). Results: Of 340 subjects enrolled, 324 were valid for safety analysis and 249 for efficacy analysis. At the short term visit, clinical cure rates for cefcanel daloxate 300 mg bid and PcV groups were similar at approximately 70%. The cure rates for cefcanel daloxate 150 mg bid and 600 mg daily were significantly worse at 57.4 and 54.4%. Approximately 80% of all pretherapy throat swabs grew bhsga . All bhsga were susceptible or intermediately susceptible to PcV and cefcanel. The bacterial elimination rate for cefcanel daloxate was 82.8% and for PcV it was 89.8%. The elimination rate was significantly lower in the cefcanel daloxate 150 mg bid and 600 mg daily groups. The clinical cure rates and the bacteriological elimination rates increased by about 10% for cefcanel daloxate 300 mg bid and the PcV groups at the last valid visit and remained significantly better than the other two cefcanel daloxate doses. Adverse events were not significantly different among the four treatment groups. Conclusions: Cefcanel daloxate 300 mg bid was as effective and as well tolerated as PcV 300 mg tid in the treatment of acute pharyngotonsillitis. A lower dose or once-daily dose regimen of cefcanel daloxate was not as effective clinically or bacteriologically.